ANALISIS EFEKTIVITAS PENGGUNAAN QR CODE PADA LKS MATEMATIKA TERHADAP PEMAHAMAN PEMBELAJARAN SISWA SDN SERANG 3 - Baheroh, Eroh; Yanti, Elprida; Sihombing, Mila Waty; Nabilla, Elsa Rosania; Masliah, Imas; Mulyani, Eli (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to analyze the effectiveness of using QR Code on mathematics Student Worksheet (LKS) on students' learning comprehension at SDN Serang 3. The research used quasi-experimental method with pretest-posttest control group design involving 42 fourth grade students. The research instruments included math concept understanding tests, student response questionnaires, and learning observation sheets. The results showed that the use of QR codes in math worksheets had a significant positive impact with a large effect size value (partial η² = 0.43) and a substantial N-gain difference between the experimental group (0.55) and the control group (0.22). The experimental group showed a higher level of engagement (78%) than the control group (53%) with a 35% increase in task time. The biggest improvement was seen in the ability to give examples and non-examples and apply concepts in problem solving. As many as 92% of students stated that math learning became more interesting and 87% reported better understanding of concepts with QR Codes. This study concludes that the integration of QR codes in mathematics worksheets is an effective strategy to improve elementary school students' understanding of mathematical concepts, with a note that infrastructure support and digital literacy need to be prepared for optimal implementation